(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
The aim of this research was to study the physiological characters of kimpul [Xanthosoma sagittifolium (L.) Schott] in various light intensity (shading) and water availability. The physiological characters are growth, photosynthetic apparatus, tissue nitrogen and polyphenol content. Information about physiological character of tannia is important in order to their cropping development. The research done in randomize complete block design with 2 factors and 3 replicates. The first factor was light intensity (shading) in 3 levels (0%, 55%, and 75%). The second factor was water availability in 4 different fields capacities (40%, 60%, 80% and 100%). The treatments were be done in 6 weeks. There were 8 parameters measured (plant height, dry plant weight, total chlorophyll content, stomata index, nitrogen and polyphenol content. The data were analyzed by analysis of varians, followed by DMRT in 5% confident level. The result showed that the plant height significantly affected by the combinations of treatment (shading and water availability). The treatment also influenced the total chlorophyll content and leaf nitrogen content. The treatment didn’t give significantly effect on stomata index, and pholyphenol content. Key words: Xanthosoma sagittifolium (L.) Schott, light intensity, water availability, growth, nitrogen content, polyphenol.